Caffeine and human performance: from molecular mechanisms to exercise and recovery - Leng, J.; Yu, J.; Li, Z.; Zhang, Y.; Cui, J. (Frontiers in Physiology, 2026)
Caffeine, the world`s most widely consumed psychoactive substance, is a well-established ergogenic aid. Its performance-enhancing effects are mediated through multiple, interacting mechanisms that follow a dose-dependent hierarchy. The primary and most significant action at common dietary doses is the antagonism of central adenosine A1 and A2a receptors. This central blockade reduces perceived effort and fatigue, increases arousal, and modulates pain perception, thereby lowering the neural cost of exercise. This central effect is complemented by secondary peripheral metabolic actions, such as the promotion of lipolysis, though their role as primary drivers in exercising humans is supported mainly by experimental models. A direct effect on skeletal muscle calcium handling occurs only at supra-physiological concentrations and is not relevant in practice. The integration of these mechanisms leads to significant but task-dependent performance outcomes. The most robust and consistent benefits are observed for aerobic endurance exercise. Effects on strength, power, and high-intensity intermittent performance are more variable and are largely mediated by neurological and perceptual factors, explaining their greater consistency in protocols involving fatigue. For sports requiring cognitive skill, caffeine reliably enhances reaction time, vigilance, and accuracy via central nervous system stimulation. The ergogenic response is highly individualized, shaped by a complex interplay of dose, timing, genetics, and habitual use. Furthermore, preliminary evidence suggests caffeine may modulate post-exercise recovery by potentially accelerating muscle glycogen resynthesis when co-ingested with carbohydrates and by improving muscle perfusion. However, leveraging any potential recovery benefit necessitates extremely careful timing to avoid sleep disruption, as protecting sleep quality is a paramount recovery priority. Future research should develop sport- and context-specific protocols, clarify long-term adaptations, and advance personalized strategies that integrate genetic, habitual, and temporal factors to maximize benefits and minimize adverse effects, reinforcing caffeine`s role as a cornerstone of evidence-based sports nutrition.